Variable star [compact disc, unabridged] - Heinlein, Robert A. (Robert Anson), 1907-1988 (Blackstone Audio, 2007)
Two young lovers are forced apart by pride, power, and the immensity of interstellar time and space, in an authorized version of an unfinished novel by the late science fiction master.